ANALYSIS OF INVESTMENT RISK IN MALUKU PROVINCE USING MEAN-VARIANCE APPROACH ON LOCAL OWN-SOURCE REVENUE (PAD) - Bakarbessy, Lusye; Talakua, Mozard Winston; Ilwaru, Venn Yan Ishak (Statistics Study Programme, Department of Mathematics, Faculty of Mathematics and Natural Sciences, University of Pattimura, 2025)
This study aims to analyze investment risks in Maluku Province using the Mean-Variance approach on the Local Own-Source Revenue (PAD) data. The method used in this study is a quantitative analysis of time-series data on PAD from 2015 to 2022. The mean-variance model is used to calculate the rate of return and risk of each PAD component and to construct an efficient frontier as a basis for optimal decision-making. The results show that the regional tax PAD component offers a high rate of return with relatively low risk, potentially making it a stable source of revenue for local governments. These findings provide a basis for optimizing PAD allocation to improve fiscal stability and the sustainability of regional development.